Atrial fibrillation in acute heart failure: A position statement from the Acute Cardiovascular Care Association and European Heart Rhythm Association of the European Society of Cardiology. Issue 4 (1st June 2020) - Gorenek (Chair), Bulent; Halvorsen, Sigrun; Kudaiberdieva, Gulmira; Bueno, Hector; Van Gelder, Isabelle C; Lettino, Maddalena; Marin, Francisco; Masip, Josep; Mueller, Christian; Okutucu, Sercan; Poess, Janine; Potpara, Tatjana S; et al.
Abstract: Atrial fibrillation and acute heart failure frequently co-exist and can exacerbate each other. Their combination leads to increased morbidity and mortality. However, the prevalence and significance, as well as the treatment, of atrial fibrillation in acute heart failure are not well studied. Management of atrial fibrillation in acute heart failure requires a multidisciplinary team approach. Treatment of underlying disease(s), identification and treatment of potentially correctable causes and precipitating factors and anticoagulation are crucial. In this article, current evidence on atrial fibrillation in the setting of acute heart failure is summarised. The recommendations on management of atrial fibrillation in the prehospital stage, the treatment of reversible causes, when and how to use rate or rhythm control, maintenance of sinus rhythm, catheter ablation and pacing, anticoagulation, as well as measures on prevention of atrial fibrillation are provided.